Digital phenotyping, behavioral sensing, or personal sensing: names and transparency in the digital age - David C. Mohr; Katie Shilton; Matthew Hotopf (npj Digital Medicine, 2020)
Abstract Data from networked sensors, such as those in our phones, are increasingly being explored and used to identify behaviors related to health and mental health. While computer scientists have referred to this field as context sensing, personal sensing, or mobile sensing, medicine has more recently adopted the term digital phenotyping. This paper discusses the implications of these labels in light of privacy concerns, arguing language that is transparent and meaningful to the people whose data we are acquiring.